Sustainable Ethanol Production From Sugarcane Molasses by Saccharomyces cerevisiae Immobilized on Chitosan-Coated Manganese Ferrite - Núñez Caraballo, Arianna; Iliná, Anna; Ramos González, Rodolfo; Aguilar, Cristóbal N.; Michelena Álvarez, Georgina; Flores Gallegos, Adriana Carolina; Sandoval-Cortés, José; Aguilar-Gonzalez, Miguel A.; Soto-Cruz, Nicolas Oscar; García García, José Daniel; Martínez-Hernández, José L. (Frontiers in Sustainable Food Systems, 2021)
The interaction between nanostructures and yeast cells, as well as the description of the effect of nanoparticles in ethanol production are open questions in the development of this nanobiotechnological process. The objective of the present study was to evaluate the ethanol production by Saccharomyces cerevisiae in the free and immobilized state on chitosan-coated manganese ferrite, using cane molasses as a carbon source. To obtain the chitosan-coated manganese ferrite, the one-step coprecipitation method was used. The nanoparticles were characterized by X-ray diffraction obtaining the typical diffraction pattern. The crystal size was calculated by the Scherrer equation as 15.2 nm. The kinetics of sugar consumption and ethanol production were evaluated by HPLC. With the immobilized system, it was possible to obtain an ethanol concentration of 56.15 g/L, as well as the total sugar consumption at 24 h of fermentation. Productivity and yield in this case were 2.3 ± 0.2 g/(L * h) and 0.28 ± 0.03, respectively. However, at the same time in the fermentation with free yeast, 39.1 g/L were obtained. The total consumption of fermentable sugar was observed only after 42 h, reaching an ethanol titer of 50.7 ± 3.1, productivity and yield of 1.4 ± 0.3 g/(L * h) and 0.25 ± 0.4, respectively. Therefore, a reduction in fermentation time, higher ethanol titer and productivity were demonstrated in the presence of nanoparticles. The application of manganese ferrite nanoparticles shows a beneficial effect on ethanol production. Research focused on the task of defining the mechanism of their action and evaluation of the reuse of biomass immobilized on manganese ferrite in the ethanol production process should be carried out in the future.